Mixed-Meal Tolerance Test Versus Glucagon Stimulation Test for the Assessment of β-Cell Function in Therapeutic Trials in Type 1 Diabetes - Greenbaum, Carla J; Mandrup-Poulsen, Thomas; McGee, Paula Friedenberg; Battelino, Tadej; Haastert, Burkhard; Ludvigsson, Johnny; Pozzilli, Paolo; Lachin, John M; Kolb, Hubert (Diabetes care, 2008)
OBJECTIVE:--β-Cell function in type 1 diabetes clinical trials is commonly measured by C-peptide response to a secretagogue in either a mixed-meal tolerance test (MMTT) or a glucagon stimulation test (GST). The Type 1 Diabetes TrialNet Research Group and the European C-peptide Trial (ECPT) Study Group conducted parallel randomized studies to compare the sensitivity, reproducibility, and tolerability of these procedures. RESEARCH DESIGN AND METHODS--In randomized sequences, 148 TrialNet subjects completed 549 tests with up to 2 MMTT and 2 GST tests on separate days, and 118 ECPT subjects completed 348 tests (up to 3 each) with either two MMTTs or two GSTs. RESULTS:--Among individuals with up to 4 years' duration of type 1 diabetes, >85% had measurable stimulated C-peptide values. The MMTT stimulus produced significantly higher concentrations of C-peptide than the GST. Whereas both tests were highly reproducible, the MMTT was significantly more so (R² = 0.96 for peak C-peptide response). Overall, the majority of subjects preferred the MMTT, and there were few adverse events. Some older subjects preferred the shorter duration of the GST. Nausea was reported in the majority of GST studies, particularly in the young age-group. CONCLUSIONS:--The MMTT is preferred for the assessment of β-cell function in therapeutic trials in type 1 diabetes.